Discovering Ethnomathematics in the Architecture of Samin Community in Jepang Bojonegoro - Ramadhan, Katon Agung; Anggraheni, Fani Yunida; Ahmadi (Pi: Mathematics Education Journal, 2026)
This study aims to analyze the mathematical values contained in the traditional house of the Samin community and determine the application to use the concepts in mathematics learning. Ethnographic approach and triangulasi method are used in qualitative research analysis. Data collection techniques were carried out by literature study, participatory observation, documentation and interviews. Triangulasi is used for data variation and validation while ethnografi is used to study and develop cultural understanding. The results showed that there are ednomathematics concepts that are relevant to be applied to mathematics learning such as the shape of the roof, poles, doors, windows and the middle room. The discovery of the concept of flat shapes (square, rectangle, triangle, trapezoid), spatial shapes (block, prism), geometrict transformations (translation, rotation, reflection), and similarity. The mathematical concept in this research can be applied to the school curriculum from elementary to high school. Practical value, this research help students understand mathematics through their own enviroment and cultural. Cultural value, ednomathematics based learning strengthens local identity and cultural presenvation. Use value, the math learning approach is more contextual, fun and relevant ro real life.